Collective Leadership of Islamic Boarding Schools on the Element of Educators - Abdul Basit; Diah Mutiara; Ummah Karimah; Thahirah Nur Adilla; Azizah Istiqomah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study intends to learn the leadership and management techniques used by Edward Sallis, the TQM champion at Darunnajah Boarding School, to gauge learners' level of contentment and then contribution of thinking to the following researchers. Case studies and other qualitative methods were used in this investigation.  Darunnajah Islamic Boarding School in South Jakarta employs a purely qualitative phenomenalogy design in their daily operations. Use data was collected by observation methods, in-depth interviews, and documentation in this study. Triangulating the data, or comparing the written data with the findings of interviews and existing observations, is one method for validating data. Data collection that has been done and data analysis process, this research found that the role of external consultants in schools at the duties of the South Jakarta Darunnajah Islamic Boarding School is to give assignments to educators and education staff during a certain temp, monitor and evaluate the performance of teachers who do not achieve learning objectives, provide additional hours, and impose sanctions for those who violate based on the management of Darunnajah. In improving the scientific competence of teachers, Islamic boarding schools provide opportunities for teachers to continue their studies from the Bachelor level to a higher level, such as Masters Two and Three. The results of this research have not been optimally carried out due to time constraints and so many problems that have been obtained. Because researchers hope that other researchers will continue so that the results are more comprehensive as what the researchers wrote about the benefits of research. Collective leadership produces excellent graduates, professional teachers, infrastructure, laboratories, canteens, student skills.